(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
Since the advent of Constitutional Amendment nº 45 of 2004, reasonable length of proceedings has become a fundamental right of Brazilian citizens to be a party, whether administrative or judicial. Replacer innovation of the Constitution and based on this inovation, came upon several programs and initiatives with the objective to provide the processes administered by the Government of efficiency and effectiveness, such as electronic trading, electronic judicial process and encouraging reconciliation. However, delays still plaguing the public agencies and the courts, so simply demands sometimes drag on for decades. And the change of the legal procedural text demand initiative and political will, predicates not always consensus among Brazilian parliamentarians. Has this text in order to present the possibility of using, among many administrative and management tools, one of the most instrumental and easy to use by the public administration, notably the judiciary, the PDCA cycle.